Nanocomposites : Materials, Manufacturing and Engineering. - Davim, J. Paulo (Advanced composites., 2013)
Composite materials are engineered materials, made from two or more constituents with significantly different physical or chemical properties which remain separate on a macroscopic level within the finished structure. Due to their special mechanical and physical properties they have the potential to replace conventional materials. In nanocomposites the size of one phase is less than 100 nm in at least one dimension. Nanocomposites with polymer, metal or ceramic matrices find increasing application in bioengineering, battery cathodes, automotives, sensors and computers.- Resumé vydavatel